An Unusual Pediatric Case of Allen Key Penetrating Trauma in Maxillofacial Region - Feride Fatma Görgülü; Orhan Görgülü; Ayşe Selcan Koç; Fatma Yasemin Öksüzler (Case Reports in Radiology)
Paranasal sinus (PNS) foreign bodies are not common. They are usually due to penetrating trauma and iatrogenic events. On imaging, radiopaque foreign bodies can easily be detected by X-ray views of PNS. CT scan may be necessary to evaluate the exact location of foreign body in some cases. Foreign body in the PNS should be removed as early as possible. Approach and technique of its removal depend upon its size, shape, and location. Nasal endoscopic examination can be helpful for these cases. We present a pediatric girl case of penetrating FB injury inserted into the maxillary sinus towards nasopharynx in a suddenly braking car.